Development and Preliminary Validation of PQC-ORI: A Public-Sector Readiness Assessment Instrument for Post-Quantum Cryptography - Fadlilah Izzatus Sabila; Fauziah (Universitas Gunadarma, 2026)
The emergence of quantum computing technologies poses significant risks to conventional public-key cryptographic systems and creating an urgent need for organizational preparation toward Post-Quantum Cryptography (PQC) migration. Although various PQC migration frameworks and quantum-readiness initiatives have been proposed, existing approaches primarily focus on technical migration guidance and provide limited operational mechanisms for assessing organizational readiness, particularly within public-sector environments. This study develops and conducts a preliminary validation of a Post-Quantum Cryptography Organizational Readiness Instrument (PQC-ORI) for Indonesian public-sector organizations using a Design Science Research approach integrating Systematic Literature Review (SLR), Qualitative Content Analysis (QCA), and Framework Alignment Matrix (FAM) techniques to synthesize recurring organizational readiness constructs from PQC migration literature, governance frameworks, and cybersecurity readiness studies. The resulting framework comprises six organizational readiness dimensions: Cryptographic Awareness, Governance and Policy, Migration Management, Technical Capability, Cryptographic Agility, and Operational Resilience. The framework additionally operationalizes these dimensions into structured assessment indicators and a five-level maturity model intended to support organizational self-assessment and migration planning activities. Preliminary validation by three domain experts using structured expert judgment yielded an overall mean score of 3.69/4.00, indicating high relevance, conceptual consistency, and applicability for assessing organizational readiness for PQC migration in public-sector organizations.